The Impact of Diagenesis and Dolomitization on the Reservoir Potential of Middle Jurassic Samana Suk Formation from Khanpur Dam Section Hazara Basin, Khyber Pakhtunkhwa Pakistan : The Impact of Diagenesis and Dolomitization on the Reservoir Potential of Middle Jurassic Samana Suk Formation from Khanpur Dam Section Hazara Basin, Khyber Pakhtunkhwa Pakistan - Maqsood Ur Rahman; Fahad Ali; Shah Faisal; Salman Khalid; Hafiz Shahid Hussian; Tanveer Ul Haq (International Journal of Economic and Environmental Geology, 2017)
Detailed study of the Samana Suk Formation has been carried out from the Khanpur Dam Section. Two lithological units have been identified in the studied section, limestone and dolomite (60% and 40% respectively). The dolomite is present in the form of beds or veins filling fracture and joints. In the field three types of dolomitization can be observed, yellowish, brown and saddle varieties. Microscopic studies reveal either partial, complete and selective dolomitization, which include (1) fine crystalline planar-euhedral, subhedral dolomite and non-planer anhedral dolomites (2) fine to medium crystalline non-planar-anhedral dolomite, (3) medium crystalline planar-euhedral dolomite, (4) coarse crystalline planar-subhedral dolomite, (5) coarse crystalline non-planar-Anhedral dolomite and (6) saddle dolomites. The dolomitic facies have intercrystalline porosity compared to limestone facies, which is characterized by inter-particles, moldic, vug, intraparticle, fractures and burrows porosities. The porosity of the limestone facies varies between 3% and 6%, which increase to 12% in the fractured samples, while the porosity of the dolomitic facies is in the range of7% and 14%. It has been concluded that the increasing porosity is the direct result of dolomitization. This interpretation is consistent with the field and petrographic observation, which indicate that dolomitization is secondary in nature. The dolomitization is the direct result of fluid along the fault plane due to tectonic loading creating pressure gradient. Keywords: Samana Suk Formation, diagenesis, dolomitization, Hazara basin, porosity analysis.